Multicultural Community Rationality in Running Religious Activities in Pandemic Times - Riza Firly Maulidyah; Agus Machfud Fauzi (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
Indonesian society is a multicultural society that lives side by side with all the differences. In Indonesia, they are presently six official religions-namely Islam, Protestant Christian, Catholicism, Hinduism, Buddhism, and Confucianism. It is this difference of belief that makes people live in peace and practice their respective religious teachings without any intention of disturbing the beliefs of others. The teaching of tolerance is also applied in one of the villages in Malang Regency, namely Peniwen Village. The majority of the population of this village are Protestant and Catholic Christians. Residents in this village always carry out religious activities in accordance with what has been ordered without any sense of demeaning other religions. The method used in this article is descriptive qualitative using Max Weber's theory of rationality. The purpose of this article is to find out the rationality of the people of Peniwen Village in carrying out religious activities during the pandemic. This happened because during the pandemic almost all activities were limited. The results of this study demonstrate that the Village residents continue to perform religious activities by implementing health protocols and upholding tolerance between different religious communities. The current health protocols regulate the number of congregants who will worship at the church, wear masks, and maintain personal distance.